2019
DOI: 10.1038/s41598-019-42928-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing neural responses towards objectified human targets and objects to identify processes of sexual objectification that go beyond the metaphor

Abstract: Objectification – reducing a someone to a something – represents a powerful and potentially damaging way in which we can see and treat others. Women are often victims of processes of objectification that occur whenever a woman is reduced to her body or certain body parts. What remains unclear is the extent to which a woman becomes an object when objectified. Using the oddball paradigm in three experiments, participants’ neural activity was measured while they analyzed frequently presented male and female human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 50 publications
1
31
0
Order By: Relevance
“…Dehumanization can be a worrying and degrading consequence of sexual objectification of women (Loughnan and Pacilli 2014;Vaes et al 2014;Vaes et al 2011). Research has established that sexually objectified women, but not men, not only are visually processed in a piecemeal fashion, similar to the processing style involved in the recognition of objects (Bernard et al 2012;Cogoni et al 2018a;Gervais et al 2012; see also Bernard et al 2013; Civile and Obhi 2016; Schmidt and Kistemaker 2015; Tarr 2013, for a debate), but also are perceived as more similar to real objects (Vaes et al 2019).…”
Section: Sexually Objectifying Media → Dehumanizationmentioning
confidence: 99%
“…Dehumanization can be a worrying and degrading consequence of sexual objectification of women (Loughnan and Pacilli 2014;Vaes et al 2014;Vaes et al 2011). Research has established that sexually objectified women, but not men, not only are visually processed in a piecemeal fashion, similar to the processing style involved in the recognition of objects (Bernard et al 2012;Cogoni et al 2018a;Gervais et al 2012; see also Bernard et al 2013; Civile and Obhi 2016; Schmidt and Kistemaker 2015; Tarr 2013, for a debate), but also are perceived as more similar to real objects (Vaes et al 2019).…”
Section: Sexually Objectifying Media → Dehumanizationmentioning
confidence: 99%
“…This possibility is consistent with research which has found that less configural face processing predicts lower attribution of humanness (Hugenberg et al 2016;Wilson et al 2018). In addition, recent research showed that sexualized women are more likely to be categorized as doll-like objects (Vaes et al 2019), so it would be interesting to examine whether the dehumanization of women with makeup might be mediated by perceptions of women as being doll-like at an early stage of person perception.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Finally, the third line of research directly compared the extent to which individuals perceive similarities between objectified human targets and objects (Morris & Goldenberg, 2015; Vaes et al, 2019). Vaes and colleagues used the oddball paradigm, in which participants’ neural activity was measured, while they categorized frequently presented male and female human stimuli and infrequently presented gender-matched doll-like objects.…”
Section: Objectification: the Strength Of The Categorization Conflictmentioning
confidence: 99%
“…This similarity can become quite literal as recent research has demonstrated. Through a direct comparison between objectified human and object stimuli, it has been shown that objectified women are visually perceived as more similar to objects compared to objectified men at a behavioral and a neural level (Vaes, Cristoforetti, Ruzzante, Cogoni, & Mazza, 2019). This result suggests that the typical human–object divide can fade, especially when women are objectified.…”
mentioning
confidence: 99%